Interpersonal Communication Dynamics Relationships Between the mother and Child With ADHD - Sofia Rizki Irma; Ani Yuningsih; Ike Junita Triwardhani; Rini Rinawati; Anne Ratnasari (Jogjakarta Communication Conference (JCC), 2026)
The mother–child relationship is a crucial foundation for a child’s growth. However, the dynamics of communication become more complex when a child has ADHD. Its characteristics—impulsivity, difficulty sustaining attention, and emotional instability—often lead to a gap in the interpretation of messages between mother and child. This condition not only triggers repeated miscommunication but also shapes interaction patterns characterized by emotional tension, excessive correction, and reactive responses from both parties. This study used a descriptive qualitative research method within a constructivist paradigm. The research informants consisted of key informants—two muslim mothers with children with ADHD and a supporting informant, a child clinical psychologist. Research data were collected through in-depth interviews and observation of the mothers’ social media. The aim of the study was to examine the role of mothers in managing their own and their children’s emotions to strengthen the relationship between mothers and children with ADHD through interpersonal communication. The results indicate that emotional regulation is a key factor in the upbringing of children with ADHD. Mothers who are able to regulate their own and their child’s emotions, and who employ reflective, consistent, and empathetic communication, successfully reduce the intensity of tantrums, improve behavioral consistency, and foster harmonious interactions. Strategies such as self-regulation, cooling down, the use of soothing touch, and communication when the child is emotionally stable have proven effective. Professional support, a conducive environment, and the integration of Islamic parenting values (patience, compassion, and setting a good example) strengthen emotional regulation in both mother and child and support the child’s overall positive character development.